Traumatological Aspect of Polytrauma Treatment for Elderly and Senile Patients - R. I. Valieva; P. A. Ivanov (Неотложная медицинская помощь)
The conducted analysis of Russian and foreign literature sources showed that the problem of diagnostics and treatment of polytrauma in elderly and senile patients is still relevant. The main discussion point is the high  mortality rate in this group of patients. Although at this level of the  medicine’s evolution, an active approach to the treatment offered to such patients is applicable, the mortality rate in this group of patients remains much higher than in the group of patients under 65. The priority here is to study the difficulties of diagnosing injuries in elderly and senile patients with  polytrauma. Also, a fundamental issue is the development of an effective algorithm for the surgical treatment of injuries, taking into  consideration agerelated changes, the presence of concomitant pathology and an increased risk of complications in patients of this age group.